Inhalation of Protium heptaphyllum (Aubl.) Marchand (BREU-BRANCO) essential oil as an analgesic and anxiolytic in fibromyalgia. Case reports - Tauany Milan Ribeiro-Lacerda; Luciana Kazue Otutumi; Cristiane Mengue Feniman Moritz; Daniela de Cassia Faglioni Boleta-Ceranto; Ezilda Jacomassi (BrJP)
BACKGROUND AND OBJECTIVES: Fibromyalgia (FM) refers to a chronic pain condition with a multifactorial etiology, which negatively impacts the lives of its sufferers and is often refractory to conventional treatment. The aim of this study is to report a series of cases using Protium heptaphyllum (OEBB) essential oil to control pain and anxiety in FM sufferers. CASE REPORTS: This is a case series of an experimental, open and self-controlled study aimed at proving the efficacy and relevance of using aromatherapy via inhalation to improve the quality of life of women with fibromyalgia (FM). For this purpose, the essential oil obtained by steam distillation of resin OEBB was used. Five women over the age of 50 with a confirmed medical diagnosis and insufficient treatment with traditional therapies were selected to verify the efficacy of inhaling OEBB essential oil. The patients were assessed using the Fibromyalgia Impact Questionnaire (FIQ) and the visual analog scale (VAS) before and after aromatherapy and the results were compared using the T-test for two related samples. The evidence showed that OEBB inhalation was not effective in reducing the intensity of pain crises (p>0.05). However, there was evidence of benefits in relation to improvements in quality of life, such as an increase in disposition, improvement in mood, restorative sleep and a reduction in anxiety in 46.78% (p<0.01), as demonstrated by the score obtained on the FIQ. CONCLUSION: It can be concluded that aromatherapy via inhalation has a positive effect on controlling the comorbidities caused by fibromyalgia. Furthermore, aromatherapy is a complementary practice that should be considered a powerful adjunct to traditional therapies, and its indication should be encouraged by public and private health services.